Factors associated with child hunger among food insecure households in Bangladesh. (December 2017) - Haque, Md; Farzana, Fahmida; Sultana, Sabiha; Raihan, Mohammad; Rahman, Ahmed; Waid, Jillian; Choudhury, Nuzhat; Ahmed, Tahmeed
Abstract Background Hunger is associated with food insecurity at the household level and is considered as a global public health problem with long term adverse consequences on children's health. This study aims to determine the factors associated with child hunger from a nationally representative sample in Bangladesh among food insecure households. Methods Data was derived from the Food Security and Nutritional Surveillance Project; 14, 712 children aged 6–59 months belonging to food insecure households contributed to the analysis. Information on food security at the household level was collected for 30 days preceding the survey. Descriptive statistics served to illustrate the variables studied and multiple logistic regression analysis was conducted to identify the significant risk factors for child hunger. Results Overall 10% of the children were found to be hungry. After adjusting for seasonality, residence type and education level of household head, the variables - female headed households [OR: 1.87 (1.43–2.45);p < 0.001], severely food insecure households [OR: 10.5 (1.43–76.6);p < 0.05], households having women with no education [OR: 1.56 (1.27–1.92);p < 0.05], poorest asset quintile [OR: 1.50 (1.11–2.15);p < 0.05] and the amount of rice consumed per household per week [OR: 0.94 (0.92–0.96);p < 0.001] were found to be significantly and independently associated with child hunger. Conclusions Out of the potential risk factors examined, our study found significant and independent association of five variables with child hunger: sex of the household head, household food insecurity status, educational status of household women and asset index. Despite all sampled household being food insecure, degree of household food insecurity status appeared to be the strongest predictor of child hunger.